Current diagnostic procedures and interventions for Gaming Disorders: A Systematic Review - Costa, Sebastiano; Kuss, Daria J. (Frontiers in Psychology, 2019)
Abstract Background: Despite the growth in the number of studies on Gaming Disorders (GD), assessing the characteristics of clinical subjects is still limited. Driven by the need to overcome this limitation, a broad systematic review is essential to cover the studies that have already assessed the clinical characteristics of individuals diagnosed with GD. Objectives: For this reason, the aim of this systematic review is to provide a broad cross-cultural picture of the current diagnostic procedures and interventions used for GDs in clinical practice. Methods: A total of 28 studies met the inclusion criteria, and the present review examined: (1) the cultural background of the country where the research took place; (2) the instruments used to measure GD; (3) the diagnostic criteria for GD; (4) the diagnostic procedures used; and (5) the treatment protocol applied. Results: Results of this systematic review suggest that in GD clinical practice, there is a great deal of heterogeneity in the choice of instruments, the diagnostic and intervention processes for GD. Conclusions: This systematic review indicates that a validation process of standard procedures in clinical populations with GD is necessary to create clear shared guidelines for practisers.